“Read That Article”: Exploring synergies between gaze and speech interaction - Vieira, D.; Freitas, J. D.; Acartürk, C.; Teixeira, A.; Sousa, F; Candeias, S.; Dias, J. (ASSETS '15: Proceedings of the 17th International ACM SIGACCESS Conference on Computers & Accessibility, 2015)
Gaze information has the potential to benefit Human-Computer Interaction (HCI) tasks, particularly when combined with speech. Gaze can improve our understanding of the user intention, as a secondary input modality, or it can be used as the main input modality by users with some level of permanent or temporary impairments. In this paper we describe a multimodal HCI system prototype which supports speech, gaze and the combination of both. The system has been developed for Active Assisted Living scenarios.